Evaluation of Water Absorption Effects on the Mechanical Properties and Sound Propagation Behavior of Polyester Matrix- Sponge Gourd Reinforced Composite - Feiferis, A. R.; d’Almeida, J. R. M. (Journal of Composites and Biodegradable Polymers, 2016)
This study aimed to evaluate the variation of the mechanical properties of a polyester matrix composite reinforced by sponge gourd fibers as a function of immersion time in water. The characterization of the composite was performed using bending mechanical test and a sonic test. The Young's modulus and the sound propagation characteristics of the composite were evaluated as a function of immersion time. The water diffusion coefficient was also determined. The results indicate that the percentage of water absorbed increases rapidly, but stabilizes at around 2 weeks after the start of the absorption process. The variation of elastic modulus and damping factor showed a direct correlation with water content in the composite, and both properties remained constant when the absorbed water content stabilized. These results were interpreted as an indication that the composites suffered only physical aging due to water absorption, at the immersion times used in this work. The mechanical properties evaluated by the bending test decreased after absorption of water, but the obtained variations were small. The results obtained indicate that the absorbed water acts as a plasticizer in this composite, but does not cause chemical aging.